The Social Justice Framework in the Information Technology Rural Librarian Master’s Scholarship Program: Bridging the Rural Digital Divides - Mehra, Bharat; Black, Kimberly; Singh, Vandana; Nolt, Jenna; Williams, K. C.; Simmons, Susan; Renfro, Nancy (Qualitative and Quantitative Methods in Libraries; 2014: Special Issue: Social Justice, Social Inclusion, 2017)
This paper applies a social justice framework to reflect on the experiences in the Information Technology Rural Librarian Master’s Scholarship Program (ITRL) that has recently been funded by the Institute of Museum and Library Services’ Laura Bush 21st Century Librarian Program to the School of Information Sciences (SIS) at the University of Tennessee (UT). ITRL’s purpose is to recruit and train sixteen paraprofessionals working in the Southern and Central Appalachian (SCA) rural libraries to complete their master’s degree part-time from June 2010 – August 2012 in the UT’s SIS synchronous distance education program.